Consumer preferences and the reliability of Euler equation tests of capital mobility: some simulation-based evidence - Christian Pierdzioch; Joerg Doepke; Claudia M. Buch (Kiel Institute for World Economics (IfW), 2002)
The globalization of international financial markets has renewed interest in the measurement of capital mobility. Consumption-based tests such as the Euler equation test are commonly used. These tests, however, are derived under restrictive assumptions on consumer behavior. In this paper, we ask how the Euler equation test of capital mobility performs if these restrictive assumptions are relaxed. We simulate a dynamic general equilibrium two-country model under alternative assumptions regarding consumer preferences and use the simulated time series to test for the degree of capital mobility. We find that the Euler equation test discriminates fairly well between high and low capital mobility regimes even if the restrictive assumptions on consumer behavior used to derive the test are not satisfied.
Keywords: F36; F41; F47; E32; G15; 330; international capital mobility; Euler equation tests; consumption smoothing; new open economy macro models; Internationale Kapitalmobilität; Euler-Gleichung; Zeitpräferenz; Zeitreihenanalyse; Neue Makroökonomik offener Volkswirtschaften; Simulation; Schaetzung; Theorie; Welt